(untitled) (Global Journal of Science Frontier Research, 2017)
Millions of years on Earth created a favorable climate. The main instrument of this construction was the balance of the circulation of various substances between the atmosphere and the biota. One of the main circuits is the movement of water. Precipitation falls in a given zone in a given volume, with a predetermined sequence. In accordance with the needs of the inhabitants of the zone. Inhabitants of these zones or biota - the community of animal and plant life - returned moisture to the sky with their breathing and transpiration. There was harmony, a certain rhythm and climatic comfort. Heating the soil leads to evaporation and increased cloudiness. Clouds shade the soil and reduce solar radiation - evaporation decreases - clouds decrease - radiation increases. Conversely, intensification of sunlight activates plant growth, development and activity of biota, increases volatility. The sun is hidden behind the clouds again. Atmospheric phenomena and biota formed an interdependent symbiosis. It is this symbiosis that created the climate of the whole planet for the weather for every point of the earth. And at every point, in accordance with the needs of its inhabitants. The atmosphere gave out exactly as much water as necessary for this area.